Approaches to Fraudulence Risk Management through Business Control and Culture - et. al., Rini Setiawati, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Culture formed in organizations will create individuals with similar values ​​and behaviors that will then form groups. If in an organization a culture is instilled that cheating is an act that is not good and will harm many parties, then employees tend not to commit fraud. This Research want to look at the impact of Business control and organizational culture on fraudulence precaution. Methodology using Partial Least Square (PLS-XLStat). The results obtained R2 of 0.677 means fraudulence precaution is influenced by 67.7% by business control and organizational culture with coefficients of 0.508 and 0.382 and significant at 5% (t value> t table 1.96). The remaining 32.3% is influenced by other variable that not included in the study. Hypothesis testing shows that business control has a positive and significant impact on fraudulence precaution. Organizational culture has a positive and significant impact.